Persepsi Petani Terhadap Kinerja Penyuluh Pertanian Padi Sawah Di Desa Pasir Jaya Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Lestari, Dian; Fitriana, Laily; Defidelwina (Universitas Pasir Pengaraian, 2023)
Efforts to increase the success of lowland rice farming are inseparable from farmers' perceptions of extension worker performance. This is because perception is closely related to a person's attitude and response to a particular object, namely the performance of agricultural extension workers. This research was conducted aiming to determine the performance of agricultural extension workers, farmers' perceptions of agricultural extension performance. The determination of the research location was purposive in Pasir Jaya Village, Rambah Hilir District, Rokan Hulu Regency. This research was conducted from January to February 2023. The sampling technique was the Simple Random Sampling method (simple random sample), the sample was 52 people taken from 110 population. Data collection methods used are observation, documentation, and direct interviews with farmers. Data analysis used in this research is descriptive analysis. Farmers' perceptions of the performance of agricultural extension workers are included in the very good category with an average score of 231.40 with an index score of 89.00%. Where the highest score is found in the indicator of evaluation and reporting of agricultural extension with a total score of 236.50 with an index score of 90.96% included in the very good category and the lowest score is in the indicator of preparation for agricultural extension with a score of 227.50 with an index score of 87.50% included in the very good category. The results showed that the implementation of agricultural extension in Pasir Jaya Village based on the activities carried out by extension agents in preparing agricultural extension, implementing agricultural extension, evaluating and reporting agricultural extension had been able to provide changes to farmers, namely changes in attitudes and skills and increased farmer productivity compared to the previous year.